The High Court Division (Bangladesh) Verdict Acknowledging Mother as Legal Guardian of a Child and its Probable Impact on the Person and the Respective Society - Akand, Mahmuda (Asian Studies, 2023)
Social values and laws, both require to evolve following better conscience and reason. Recently, the High Court Division of Bangladesh has ruled that mothers can be the sole guardian of children. Before this verdict, only fathers were considered as legal guardians in Bangladesh and it was a practice that an individual, a child or a student, will be identified by father’s identity only. This paper shows that this verdict has not only provided an individual, in Bangladesh, with the opportunity to be identified only by mother’s identity, in required cases, but also has created an opportunity to rethink about the idea of individual identity which may influence the perceptions of Bangladeshi society regarding identity, human dignity and gender relations.